Determinants of recurrence after intended curative resection for colorectal cancer. (December 2014) - Wilhelmsen, Michael; Kring, Thomas; Jorgensen, Lars N.; Madsen, Mogens Rørbæk; Jess, Per; Bulut, Orhan; Nielsen, Knud Thygesen; Andersen, Claus Lindbjerg; Nielsen, Hans Jørgen
Abstract Despite intended curative resection, colorectal cancer will recur in ∼45% of the patients. Results of meta-analyses conclude that frequent follow-up does not lead to early detection of recurrence, but improves overall survival. The present literature shows that several factors play important roles in development of recurrence. It is well established that emergency surgery is a major determinant of recurrence. Moreover, anastomotic leakages, postoperative bacterial infections, and blood transfusions increase the recurrence rates although the exact mechanisms still remain obscure. From pathology studies it has been shown that tumors behave differently depending on their location and recur more often when micrometastases are present in lymph nodes and around vessels and nerves. K-ras mutations, microsatellite instability, and mismatch repair genes have also been shown to be important in relation with recurrences, and tumors appear to have different mutations depending on their location. Patients with stage II or III disease are often treated with adjuvant chemotherapy despite the fact that the treatments are far from efficient among all patients, who are at risk of recurrence. Studies are now being presented identifying subgroups, in which the therapy is inefficient. Unfortunately, only few of these facts are implemented in the present follow-up programs. Therefore, further research is urgently needed to verify which of the well-known parameters as well as new parameters that must be added to the current follow-up programs to identify patients at risk of recurrence.